Desmocollin-1 is associated with pro-metastatic phenotype of luminal A breast cancer cells and is modulated by parthenolide - Lapcik, Petr; Sulc, Petr; Janacova, Lucia; Jilkova, Katerina; Potesil, David; Bouchalova, Pavla; Müller, Petr; Bouchal, Pavel (Cellular & molecular biology letters, 2023)
BACKGROUND: Desmocollin-1 (DSC1) is a desmosomal transmembrane glycoprotein that maintains cell-to-cell adhesion. DSC1 was previously associated with lymph node metastasis of luminal A breast tumors and was found to increase migration and invasion of MCF7 cells in vitro. Therefore, we focused on DSC1 role in cellular and molecular mechanisms in luminal A breast cancer and its possible therapeutic modulation. METHODS: Western blotting was used to select potential inhibitor decreasing DSC1 protein level in MCF7 cell line. Using atomic force microscopy we evaluated effect of DSC1 overexpression and modulation on cell morphology. The LC-MS/MS analysis of total proteome on Orbitrap Lumos and RNA-Seq analysis of total transcriptome on Illumina NextSeq 500 were performed to study the molecular mechanisms associated with DSC1. Pull-down analysis with LC-MS/MS detection was carried out to uncover DSC1 protein interactome in MCF7 cells. RESULTS: Analysis of DSC1 protein levels in response to selected inhibitors displays significant DSC1 downregulation (p-value ≤ 0.01) in MCF7 cells treated with NF-κB inhibitor parthenolide. Analysis of mechanic cell properties in response to DSC1 overexpression and parthenolide treatment using atomic force microscopy reveals that DSC1 overexpression reduces height of MCF7 cells and conversely, parthenolide decreases cell stiffness of MCF7 cells overexpressing DSC1. The LC-MS/MS total proteome analysis in data-independent acquisition mode shows a strong connection between DSC1 overexpression and increased levels of proteins LACRT and IGFBP5, increased expression of IGFBP5 is confirmed by RNA-Seq. Pathway analysis of proteomics data uncovers enrichment of proliferative MCM_BIOCARTA pathway including CDK2 and MCM2-7 after DSC1 overexpression. Parthenolide decreases expression of LACRT, IGFBP5 and MCM_BIOCARTA pathway specifically in DSC1 overexpressing cells. Pull-down assay identifies DSC1 interactions with cadherin family proteins including DSG2, CDH1, CDH3 and tyrosine kinase receptors HER2 and HER3; parthenolide modulates DSC1-HER3 interaction. CONCLUSIONS: Our systems biology data indicate that DSC1 is connected to mechanisms of cell cycle regulation in luminal A breast cancer cells, and can be effectively modulated by parthenolide.
Keywords: Desmocollins; proteom; Tandem Mass Spectrometry; desmokoliny; MFC-7 buňky; Neoplasms; nádory; Proteome; lidé; MCF-7 Cells; Chromatography, Liquid; Sesquiterpenes; seskviterpeny; Proteomics; tandemová hmotnostní spektrometrie; Metastasis; DSC1; Pull-down; Breast cancer; DIA; chromatografie kapalinová; Humans